2009
DOI: 10.1203/pdr.0b013e31819dba91
|View full text |Cite
|
Sign up to set email alerts
|

The Vitamin D Connection to Pediatric Infections and Immune Function

Abstract: ABSTRACT:Over the past 20 y, a resurgence in vitamin D deficiency and nutritional rickets has been reported throughout the world, including the United States. Inadequate serum vitamin D concentrations have also been associated with complications from other health problems, including tuberculosis, cancer (prostate, breast, and colon), multiple sclerosis, and diabetes. These findings support the concept of vitamin D possessing important pleiotropic actions outside of calcium homeostasis and bone metabolism. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
186
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(191 citation statements)
references
References 72 publications
0
186
0
5
Order By: Relevance
“…The relationship between vitamin D and asthma has been known for a long time. Although the mechanism is not known, new studies have found an association between high vitamin D levels and better lung functions, lower respiratory tract hypersensitivity and increased glucocorticoid responses (17).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between vitamin D and asthma has been known for a long time. Although the mechanism is not known, new studies have found an association between high vitamin D levels and better lung functions, lower respiratory tract hypersensitivity and increased glucocorticoid responses (17).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence for an inverse correlation between URI incidence and 1,25(OH) 2 D3 serum levels, regardless of season [7]. Vitamin D has been also shown to have effects on the innate immune response, inhibiting proliferation of Mycobacterium tuberculosis in macrophages [6], and the majority of M. tuberculosis patients has low levels of serum vitamin D, supplementation of which results in greater clinical improvement than standard therapy alone [8]. Other studies have suggested a link between vitamin D insufficiency and autoimmune diseases such as multiple sclerosis and Crohn's disease [6] which may possibly be because vitamin D3 enhances Th2 differentiation at the expense of Th1 cells [9].…”
mentioning
confidence: 99%
“…23 Vitamin D status during pregnancy also has strong correlation with innate immune response of fetus. 24 Vitamin D plays important role in prevention of respiratory diseases like respiratory distress syndrome, pneumonias, wheezing episodes, asthma in later life. Vitamin D also has a role in prevention of acute lower respiratory infections in toddlers.…”
Section: Discussionmentioning
confidence: 99%